Pentingnya identitas nasional dalam era globalisasi: menjaga jati diri bangsa di tengah arus perubahan - Nabilah, Carina Nasywa (Maliki Interdisciplinary Journal, 2025)
Globalization is an inevitable process in the development of the modern world, bringing significant impacts on various aspects of life such as social, cultural, economic, and political spheres. Amid the rapid flow of globalization, the importance of maintaining and strengthening national identity becomes increasingly essential. National identity is the character of a nation that reflects the values, norms, culture, and history that shape the character of its society. In the Indonesian context, the influence of globalization can threaten the preservation of the nation’s noble values if there is no awareness of the importance of defending national identity. This study aims to examine the urgency of national identity in facing globalization and to identify strategies to strengthen the nation’s character. Using a qualitative-descriptive approach, this study emphasizes that character education, the preservation of local culture, and the reinforcement of Pancasila values are strategic steps that must continually be pursued. With a strong identity, the Indonesian nation is not only able to withstand the waves of global change but also to demonstrate its existence as a sovereign, cultured, and dignified nation. Therefore, national identity must serve as the main foundation in the nation-building process to remain resilient and not be eroded by the ongoing global currents.